Projects with Significant Expected Restructuring Effects - Mackie, Peter; Nellthorp, John; Laird, James (World Bank, Washington, DC, 2012)
This note focuses on the economic evaluation of more conventional infrastructure investments, and specifically on two types of projects which may result in significant economic restructuring - relocation of economic activities, generation of new activities, or changes in the way that current activities are undertaken. The two examples used: new urban rail lines and major new barrier crossings serve simply as examples of a much wider issue. The issue is that whenever projects bring about a large step change in transport costs, there is a stimulus for a reorganization of economic activity outside the transport sector.